These two Z-transform properties are relevant

$\displaystyle x[n-n_0] \Longleftrightarrow z^{-n_0}X(z)$

$\displaystyle nx[n] \Longleftrightarrow -z \frac{dX(z)}{dz}$

yet I don't know how (in which order) one should apply them on the following:

$\displaystyle Z(n u[n - N])$

Even using the z-transform definition, I cannot get a closed form solution:

$\displaystyle Z(n u[n - N]) = \sum_{n=-\infty}^{\infty} n u[n-N] z^{-n} = \sum_{n=N}^{\infty} n z^{-n} = \sum_{n=0}^{\infty} n z^{-n} - \sum_{n=0}^{N-1} n z^{-n} = \frac{z^{-1}}{(1-z^{-1})^2 } - \sum_{n=0}^{N-1} n z^{-n} = ?$

Is there a closed form of $\displaystyle \sum_{n=0}^{N-1} n z^{-n} = z^{-1} + 2z^{-2} + ... + (N-1)z^{-(N-1)}$ ? What is it?

PS. Is there a more suitable sub-forum I should be posting these DSP questions? Or is this it?